THE NATURE OF FLIPPED CLASSROOM IN ISLAMIC RELIGIOUS EDUCATION: A CONCEPTUAL REVIEW AND ITS IMPLICATIONS FOR PAI LEARNING - Jalaluddin; Rafizal; Syarifah Rahmah; Nia Wardhani (RADJA PUBLIKA, 2025)
Abstract This aim For study the essence of the flipped classroom model in the context of Islamic Religious Education (PAI) as well the implications to process and quality learning . Problems main points raised is need will innovation Islamic Religious Education learning that is capable answer challenge development technology , characteristics participant educate 21st century , as well as demands participant - centered learning​ education . Research This use method study library research with analyze various source scientific in the form of books , articles journal national and international , as well as document relevant research that discusses flipped classrooms and Islamic Religious Education learning . The results of the study show that the flipped classroom has suitability philosophical and pedagogical with principles Islamic Education learning , such as strengthening understanding , internalization values , independence learning and optimization interaction educational in the classroom . Implications implementation of flipped classroom in Islamic Education learning includes change the role of teachers as facilitator , improvement involvement active participant educate , and utilization technology in a way meaningful For support objective Islamic education . Findings This confirm that the flipped classroom is alternative strategic in reconstruct Islamic Religious Education learning to be more adaptive , contextual , and effective .